FEMALE ENTREPRENEUR’S CHARACTERISTIC, FINANCIAL LITERACY AND RELIGIOSITY ON FUNDING DECISIONS - Rida Rahim; Amanda Reskillah; Nasfi Nasfi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to examine the effect of entrepreneur characteristics, financial literacy, and religiosity on the decisions about female entrepreneurship funding in the creative industries in West Sumatra. It used the non-probability sampling techniques with the purposive sampling criteria, involving 130 female entrepreneurs as respondents. The study found that there was an influence of age, income, and personal financial literacy variables on the decision of female entrepreneurship funding in the creative industries in the province. This research is beneficial for women running businesses in creative industries in West Sumatra with the handicraft and fashion industries benefiting the most as the results of this study can be used as additional information in selecting the optimal sources for business financing